Prospecção de proteínas envolvidas no amadurecimento pós-colheita da graviola (Annona muricata L.) - Oliveira, Geórgia Mesquita de (2011)
The soursop (Annona muricata L.) fruit is widely used in food, because it provides vitamins, carbohydrates, proteins, lipids and other molecules for human nutrition. In recent years, soursop (exotic tropical fruit) has had a prominent position in the Brazilian economy, especially for northeastern states such as, Ceara, Alagoas, Bahia and Pernambuco. The high production of soursop fruit is mainly in the Northeast by flowering occurs throughout the year, however it is estimated that the post-harvest losses reach 50% of production, as with other native or exotic fruits. Such post-harvest losses of the product are due to the accelerated rate of development and senescence of the fruit. Although some studies on Graviola, biochemical and molecular understanding of the maturation process is very limited making it important to move forward on this knowledge to develop strategies for increasing the shelf life of fruit. In this study, we sought a better protocol for protein extraction from soursop pulp to generate two-dimensional maps and identification of potential proteins involved in post-harvest ripening of the fruit. The soursop fruit in pre-climacteric stage were collected and allowed to ripen at 25 ° C for up to 8 days. Samples of the fruit pulp were collected at 0, 2, 4, 6 and 8 days post-harvest and used for protein extraction and establishment of two-dimensional gels (2D). Two different protein extraction methods were tested and the best one concerning performance and spots with good resolution in two-dimensional gel was chosen for protein analysis. The two-dimensional gels were analyzed using the Image Master for the identification of specific or differential spots, as well as determination of their isoelectric points (IPs) and their molecular masses (MM). The pI and MM data were used to track homologous proteins in angiosperms through searches on databases UniProtKB / Swiss-Prot and UniProtKB / Tremble featuring more than 16 million deposited information. 2D gels initially produced in the pH range 3 to 10 revealed the protein concentrated in the more acidic pHs. This fact determined the pH range 4-7 was used for better separation of spots in the following analysis. After two-dimensional gel analysis of 21 specific spots and 6 differential spots were selected. The analysis in databases allowed inferences about 26 proteins. Among these proteins, several were related to fruit ripening in other species such as proteins with expression regulated by ethylene, protein related to the establishment of the organoleptic characteristics of the fruit and proteins of energy metabolism. With respect to the metabolism of proteins glycolytic pathway, Krebs cycle and ETC were inferred. Previous studies on the participation of the alternative pathway of electrons in the ripening of climacteric graviola have been strengthened. However, this study also showed that in addition to the alternative oxidase (AOX), other components may participate in the regulation of this pathway. The results reveal possible protein targets for the development of strategies and biochemical and molecular control of postharvest ripening of soursop.